Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1890/es14-00433.1
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific phenological responses to winter temperature and precipitation in a water‐limited ecosystem

Abstract: Abstract. Phenology is the study of seasonal biological events such as flowering, leaf-out, insect emergence, and animal migration. Long-term observational studies at numerous temperate zone sites have found that the timing of phenological events responds to temporal variation in climate. To assess the phenological effects of climatic variation on California's flora, The California Phenology Project (CPP) was established in 2010 to develop and to test monitoring protocols and to create tools to support long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…For example, recent work by Mazer et al . () in semi‐arid regions of California found that, for some species and phenophases, precipitation played a primary role in predicting the onset of vegetative growth or flowering; however, this study also detected complex monthly interactions between temperature and precipitation that influenced the onset of phenological transitions.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…For example, recent work by Mazer et al . () in semi‐arid regions of California found that, for some species and phenophases, precipitation played a primary role in predicting the onset of vegetative growth or flowering; however, this study also detected complex monthly interactions between temperature and precipitation that influenced the onset of phenological transitions.…”
Section: Introductionmentioning
confidence: 62%
“…In the arid and semi-arid ecosystems of the western United States, seasonal moisture can play either an interactive or a primary role in triggering vegetative and reproductive activity in plants (Beatley 1974;Kemp 1983). For example, recent work by Mazer et al (2015) in semi-arid regions of California found that, for some species and phenophases, precipitation played a primary role in predicting the onset of vegetative growth or flowering; however, this study also detected complex monthly interactions between temperature and precipitation that influenced the onset of phenological transitions.…”
Section: Introductionmentioning
confidence: 99%
“…) and plant phenology is strongly correlated with temperature and rainfall availability (Mazer et al. ), thus co‐occurring plant species are predicted to encounter similar climatic conditions and flower at similar times. Despite this expectation we observe notable phenological isolation among heterospecific populations that exist within areas of immediate range overlap (truex¯ BS phenology = 0.22; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the current body of phenological research has been conducted in temperate regions, resulting in an incomplete snapshot of how ongoing climate change will affect a diversity of vulnerable and dynamic ecosystems, such as arid environments. Although spring phenology is advancing in many temperate regions (Schwartz et al., ), in the Southwestern USA onset may be delayed in some species and respond variably across species and life cycle events (see e.g., Crimmins et al., ; Diez et al., ; Mazer et al., ). Given that the climate in the Southwest is projected to become hotter with longer, more intense droughts (MacDonald, ), a more thorough understanding of arid ecosystem phenology is critical for informing management decisions and for understanding the potential vulnerability of populations to a changing climate.…”
Section: Description Of Phenological Traits Analyzed At the Individuamentioning
confidence: 99%